FUNGSI SISTEM MANIBOB DALAM KEHIDUPAN ORANG BIAK - Hapsari, Windy (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2011)
For the Biak people, manibob means friend. Manibob is a trade relation, whereas manibob system is a system in which two individuals from two villages or two different locations to see each other through trade relations. Trade relations in the exchange system without use the currency values. The meeting can take two different individuals on closer ties and old. Problems in this paper is whether the system manibob functions in the lives of Biak. The core of this manibob system is a form of reciprocity in Biak people who reactivate the social relations in society.